Two new species of Scirtothrips genus-group (Thripidae) of Northern Peninsular Malaysia - Ng, Y.f.; Mound, L.a. (Zootaxa, 2016)
The survey of Thysanoptera in peninsular Malaysia has been concentrated largely in areas growing crops and flowers around Kuala Lumpur, and the Cameron Highlands, and there are few records of these insects from native forests particularly in the northern part of the country. The two species described here were collected during a recent visit to Belum-Temengor Forest Complex, in Perak State, part of the second largest forested area on the peninsular, and connected to the Bang Lang National Park, in Yala Province, Thailand. This forest has been well known as home to a number of endangered animals, including Malayan tigers and Asian elephants, as well as remarkable plant species such as Rafflesia with the world’s largest flowers (Abdullah et al. 2011). Despite this, forest areas are facing a major challenge from the insatiable demand for timber, palm oil and minerals, with an 80% increase in deforestation rate in Malaysia between 1990 and 2005 (FAO 2010). Forested land in peninsular Malaysia has been estimated at 5.88 million-ha or 44% of total area, but the coverage of reserved virgin forest is about 0.40 % or 23,002-ha (Dahlan 2008).